Postoperative complications in craniomaxillofacial reconstruction with medpor - De Moraes Ferreira, Ana Carulina Rezende [UNESP]; Munoz, Xiomara Monica Johanna Palacio [UNESP]; Okamoto, Roberta; Pellizer, Eduardo Piza [UNESP]; Garcia, Idelmo Rangel [UNESP] (Wolters Kluwer, 2016)
Bone reconstruction in craniofacial surgery is a challenge for surgeons, who most commonly adopt the autogenous bone grafting and alloplastic implants in such procedures. Among the alloplastic materials, the high-density porous polyethylene is highlighted-Medpor (Medpor, Porex Surgical Inc, Newman, GA), considered to be pure polyethylene, with only 1 manufacturing process and standard pore size. The purpose of the current study has been to present through a review of literature and the types of complications derived from the use of Medpor in craniomaxillofacial bone surgery. A specific and sensitive database was initially created via PubMed, focusing on studies published in English peerreviewed journals between 2004 and 2014, including case reports, experimental studies in humans, and prospective and retrospective studies. Forty articles were found at PubMed database. After analyzing their abstracts, 19 were selected, totaling 1453 patients and 121 complications, being the most commonly reported diplopia with 56 patients and infection with 6 patients. Most of the complications reported in the articles used for the development of the current review are not directly related to the use of the Medpor implant. The only complications directly related to the use of this biomaterial were cases of infection.
Keywords: Bone reconstruction; Medpor; Postoperative complication